KARAKTERISTIK PENDERITA MENINGITIS ANAK YANG DIRAWAT INAP DI RUMAH SAKIT SANTA ELISABETH MEDAN TAHUN 2010-2014 - rolentina simanullang; Sori Muda Sarumpaet; Rasmaliah . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2015)
ABSTRACTMeningitis is one of infection diseases that can not be preventing yet and stillbecomes a problem in developing country. In Indonesia, cases of death because of Meningitisfor every ages with the 17th position ( 0,8%) and for baby at the age 9-11 month (9,3%). InMedan there were 102 cases of Meningitis of children in 2006-2010.The purpose of this study with case series design is to analyze the characteristics ofthe children patients with Meningitis who were hospitalized in St. Elisabeth hospitals in 2010-2014. The population of research was 89.The result of this study reveals that the highest proportion based on age group <5years old (60,7%); male (56,2%), with sex ratio 1,3; is parents occupation entrepreneur(23,6%); Batak (78,7); Christian (58,2%); out of Medan (58,4%); the history of Tuberculosis(18%); unconscious (74,2%); Serous Meningitis (64,0%); fever (52,8%); lethargy (74,2%);own expense (96,6%); average length of treatment was 8,57 days; recovery (37,1%); deadpatient of Meningitis (CFR= 59,1%).The result of Chi-square test, reveals that the male wassignificant than female (χ2=5,000, p=0,025, 50 people vs 39 people); the average duration ofSerous Meningitis treatment was significantly longer than Purulent Meningitis (t=-2,883,p=0,006, 10,39 days vs 5,34 days).It is suggested to parents who have babies and under five-year-old children to payattention with environmental cleanness around the children to decrease the source ofcontagion and pay attention to nutrition to increase immunity.. To St. Elisabeth Hospital, it isexpected to complete the medical record, especially things related to Meningitis for children;for instance, the previous history of disease.